Improved facial feature sets for enhancing face recognition system - Bai, S.PrincySuganthi; Latha, Dr. D. PonmaryPushpa (International Journal of Engineering and Technology, 2018)
Face recognition is the vogue technology in the field of biometrics for providing surveillance facility, which is most needed in public and domestic places. With the upcoming robust algorithms for face recognition, following are the challenges noted and that have a major impact in facial recognition system such as illumination variation, pose, expression, weight variation, plastic surgery etc… that must be redefined by using long-lasting feature set and efficient classifier that suits well for the feature set.